Magnitude and Determinants of Postpartum Hemorrhage in Sub-Saharan Africa: A Systematic Review and Meta-Analysis - Enos Moyo; Tafadzwa Dzinamarira; Perseverance Moyo; Grant Murewanhema; Andrew Ross (Clinical and Experimental Obstetrics & Gynecology)
Background: Maternal mortality remains a major challenge in sub-Saharan Africa (SSA), accounting for 70% of world's maternal deaths. Hemorrhage is the leading direct cause of maternal mortality worldwide, with postpartum hemorrhage (PPH) responsible for more than two-thirds of hemorrhage-related deaths. This systematic review and meta-analysis integrated data from studies conducted in SSA to provide an accurate estimation of the prevalence of PPH and to identify regional risk variables. Methods: We conducted a search across multiple databases for peer-reviewed articles published between 2013 and 2023. This study included quantitative research employing cross-sectional, case-control, or cohort designs, regardless of sample size, and published in English. This review excluded literature reviews, meta-syntheses, qualitative studies, editorials, systematic reviews, and meta-analyses. We used MetaXL to estimate the pooled magnitude of PPH in SSA, and employed the Q test, I2 statistic, and funnel plots to assess statistical heterogeneity. Furthermore, we used MetaXL to perform subgroup and sensitivity analyses. Finally, we used IBM SPSS Statistics for Windows (Version 29.0.2.0 Armonk, NY, USA), to estimate the pooled effect size of the factors associated with PPH. Results: 26 methodologically rigorous articles were included in this review and meta-analysis. The pooled magnitude of PPH in SSA was 8.6%. The studies exhibited significant heterogeneity. Individual factors associated with PPH include the woman's age (crude odds ratio [OR] = 4.37, 95% confidence interval [95% CI] = 3.03–6.29), place of residence (OR = 2.06, 95% CI = 1.51–2.82), and parity (OR = 3.13, 95% CI = 1.38–7.11). Antenatal factors include antenatal care (ANC) attendance (OR = 3.43, 95% CI = 1.12–10.05), antepartum hemorrhage (APH) (OR = 6.83, 95% CI = 3.64–12.80), and twin pregnancy (OR = 8.25, 95% CI = 3.80–17.92). Intrapartum factors include induction of labor (OR = 4.39, 95% CI = 2.01–9.61), and mode of delivery (OR = 2.61, 95% CI = 1.80–3.78). Postpartum factors include previous history of PPH (OR = 10.86, 95% CI = 3.71–31.84), and oxytocin use after delivery (OR = 0.17, 95% CI = 0.09–0.32). Conclusions: The pooled magnitude of PPH in SSA in this study was considerably higher than that in other regions. Therefore, there is a need to strengthen strategies aimed at improving ANC attendance in SSA to ultimately reduce PPH. Additionally, close monitoring of women with risk factors for PPH and the careful use of oxytocin for labor induction are strategies that can also be used to reduce PPH in SSA.